2016
DOI: 10.1007/s41019-016-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

Landmark-Based Route Recommendation with Crowd Intelligence

Abstract: Route recommendation is one of the most widely used location-based services nowadays, as it is vital for nicedriving experience and smooth public traffic. Given a pair of user-specified origin and destination, a route recommendation service aims to provide users with the routes of the best travelling experience according to given criteria. However, even the routes recommended by the big-thumb service providers can deviate significantly from the ones travelled by experienced drivers, which motivates the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…This paper uses the orientation problem to return an optimal travel route for the user, considering the interest preference of users and the popularity of POI. The personalized recommendation method proposed in this paper incorporates two social factors: preferences of user in travelogue graphic information and interpersonal interest similarity [27]. Therefore, we first introduce the user interest factors.…”
Section: Basic Definitionmentioning
confidence: 99%
“…This paper uses the orientation problem to return an optimal travel route for the user, considering the interest preference of users and the popularity of POI. The personalized recommendation method proposed in this paper incorporates two social factors: preferences of user in travelogue graphic information and interpersonal interest similarity [27]. Therefore, we first introduce the user interest factors.…”
Section: Basic Definitionmentioning
confidence: 99%
“…The evaluation results showed that the proposed system can recommend the best route based on user feedbacks. Zheng et al [146] extended the CrowdPlanner system by proposing some strategies to verify truths and know the best routes near the locations and dealing with text queries more efficiently. Besides, it evaluated route trip by mapping services with popular route-mining algorithms.…”
Section: ) Travel Route Recommendationsmentioning
confidence: 99%
“…Generally, there are two different types of memory-based CF approaches: user based [30,32] and item based [3]. The user-based CF model can be used in POI recommendation by calculating the the probability of visiting all pairwise POIs 4 [40,41] for estimating the probability that a user checks in a new POI. Different from using user-item rating records in classical matrix factorization approaches, another model [20] is based on check-in frequency that quantifies users' preference on locations.…”
Section: Collaborativementioning
confidence: 99%